The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep04688
|View full text |Cite
|
Sign up to set email alerts
|

The Acyclic Retinoid Peretinoin Inhibits Hepatitis C Virus Replication and Infectious Virus Release in Vitro

Abstract: Clinical studies suggest that the oral acyclic retinoid Peretinoin may reduce the recurrence of hepatocellular carcinoma (HCC) following surgical ablation of primary tumours. Since hepatitis C virus (HCV) infection is a major cause of HCC, we assessed whether Peretinoin and other retinoids have any effect on HCV infection. For this purpose, we measured the effects of several retinoids on the replication of genotype 1a, 1b, and 2a HCV in vitro. Peretinoin inhibited RNA replication for all genotypes and showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recently, a new target of ACR was elucidated in an in vitro study by using Huh-7.5 cells infected with HCV-RNA [76]. This study revealed that ACR inhibits HCV-RNA replication and infectious virus release by modulating several aspects of lipid metabolism, such as triglyceride abundance and the expression of mature sterol regulatory element-binding protein 1c (SREBP1c).…”
Section: Molecular Mechanism Of Acr In Chemoprevention Of Hepatocellumentioning
confidence: 99%
“…Recently, a new target of ACR was elucidated in an in vitro study by using Huh-7.5 cells infected with HCV-RNA [76]. This study revealed that ACR inhibits HCV-RNA replication and infectious virus release by modulating several aspects of lipid metabolism, such as triglyceride abundance and the expression of mature sterol regulatory element-binding protein 1c (SREBP1c).…”
Section: Molecular Mechanism Of Acr In Chemoprevention Of Hepatocellumentioning
confidence: 99%
“…Our group and others have observed that ACR may suppress cell growth or inhibit hepatitis C virus replication by altering energy production and lipid metabolism in hepatocellular carcinoma cell lines (18,19). However, in vitro study in malignant cells provides limited information to understand the mechanism of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoid acids have been implicated in clinical applications, both as a potential antitumor agent and for the treatment of skin diseases (15). In addition, there have been a number of studies suggest that the retinoic acid or its analogues exhibit antiviral activities against a variety of pathogens, including human immunodeficiency virus type 1 (HIV-1) (16,17), measles virus (18), human herpesvirus 8 (HHV-8) (19), hepatitis C virus (HCV) (20)(21)(22), and adenovirus (23). Particularly, acitretin has been used to treat patients with HIV who have psoriasis (17,24), and the drug is well tolerated.…”
Section: Discussionmentioning
confidence: 99%